Implementasi BK Dalam Mengembangkan Kecerdasan Emosional & Spiritual Siswa Di SMAN 1 Cipeundeuy Kab Subang - Ratnawulan, Teti; Hidayat, Ayi Najmul; Kurniawan, Iwan; Adawiah, Siti Robiah (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The development of students' emotional and spiritual capacity is the main foundation for character building in the educational environment. This study focuses on examining the implementation of Guidance and Counseling (BK) services in fostering students' emotional and spiritual intelligence at SMAN 1 Cipeundeuy, Subang Regency, as well as examining the elements that play a supporting or hindering role. The approach used is descriptive qualitative, with data collection through field observations, in-depth interviews, and document searches. Data processing is carried out through the stages of data reduction, data presentation, and conclusion formulation, while the validity of the findings is tested using triangulation techniques. The results of the study show that counseling services have been implemented in line with basic educational principles and are supported by solid cooperation between counselors, homeroom teachers, and subject teachers. Efforts to strengthen emotional intelligence are directed through collaborative strategies, including the involvement of parents in certain guidance activities. The spiritual dimension was developed through various programmed religious activities, such as habitual prayer, congregational prayer, morning zikr, the Friday Blessing program, infaq and almsgiving, and the recitation of Asmaul Husna every morning. Overall, the guidance counseling services at SMAN 1 Cipeundeuy contribute significantly to the emotional and spiritual development of students, with success supported by synergy among educational actors and consistency in religious programs.ABSTRAKPembentukan kapasitas emosional dan spiritual peserta didik menjadi fondasi utama dalam penguatan karakter di lingkungan pendidikan. Penelitian ini difokuskan pada pengkajian pelaksanaan layanan Bimbingan and Counseling (BK) dalam menumbuhkan kecerdasan emosional dan spiritual siswa di SMAN 1 Cipeundeuy Kabupaten Subang, sekaligus menelaah unsur-unsur yang berperan sebagai pendukung maupun penghambatnya. Pendekatan yang digunakan adalah descriptive qualitative, dengan pengumpulan data melalui pengamatan lapangan, wawancara mendalam, serta penelusuran dokumen. Pengolahan data dilakukan melalui tahapan data reduction, penyajian data, dan perumusan simpulan, sementara keabsahan temuan diuji menggunakan teknik triangulasi. Hasil kajian menunjukkan bahwa praktik layanan BK telah dilaksanakan sejalan dengan prinsip-prinsip dasar pendidikan dan didukung oleh kerja sama yang solid antara guru BK, wali kelas, serta guru mata pelajaran. Upaya penguatan kecerdasan emosional diarahkan melalui strategi kolaboratif, termasuk pelibatan orang tua dalam pembinaan tertentu. Adapun dimensi spiritual dikembangkan melalui berbagai kegiatan religius yang terprogram, seperti pembiasaan doa, shalat berjamaah, dzikir pagi, program Jumat Berkah, infak dan sedekah, serta pemutaran Asmaul Husna setiap pagi. Secara keseluruhan, layanan BK di SMAN 1 Cipeundeuy memberikan kontribusi nyata terhadap perkembangan emosional dan spiritual siswa, dengan keberhasilan yang ditopang oleh sinergi antarpelaku pendidikan dan konsistensi program keagamaan.